2001
DOI: 10.1159/000048542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cefepime and Meropenem on the Gastrointestinal Colonization ofSurgical Patients by <i>Candida albicans</i>

Abstract: Background: The study evaluated the effects of cefepime and meropenem on the gastrointestinal (GI) colonization of surgical patients by Candida albicans. Patients and Methods: Twenty adult surgical patients who received intravenously either of these antibiotics as monotherapy for the treatment of an existing infection were studied prospectively. Ten patients received cefepime (2.0 g twice a day), and another ten meropenem (1.0 g every 8 h) for 7 days. Quantitative stool cultures for C. albicans were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Similarly, the results of the present study are in agreement with those obtained earlier by our team when meropenem was used in surgical patients [14], demonstrating that this antibiotic does not increase significantly the risk of candidiasis originating in the GI tract. Similar findings have also been described by other investigators who examined the effect of meropenem in the intestinal microflora [15].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the results of the present study are in agreement with those obtained earlier by our team when meropenem was used in surgical patients [14], demonstrating that this antibiotic does not increase significantly the risk of candidiasis originating in the GI tract. Similar findings have also been described by other investigators who examined the effect of meropenem in the intestinal microflora [15].…”
Section: Discussionsupporting
confidence: 93%
“…Using the same mouse model we have shown that under similar circumstances the three broad‐spectrum carbapenems (meropenem, imipenem and ertapenem) induce a substantial increase in the intestinal concentration of C. albicans , although dissemination of the yeast to internal organs did not occur 16,17 . Our team and other investigators have tested some of the drugs of the present study and have reported similar findings in humans 14,18–20 …”
Section: Discussionsupporting
confidence: 76%
“…16,17 Our team and other investigators have tested some of the drugs of the present study and have reported similar findings in humans. 14,[18][19][20] Furthermore, this is the first study evaluating and comparing directly the effects of the four carbapenems alone or in combination with amikacin on the GI Table 2 Effect of antibiotics on GI colonisation of mice by Candida albicans.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its claimed limited potential to induce resistance should result in fewer secondary infections and better outcomes [29,41] . Numerous clinical trials on cefepime for the treatment of various infections have generally shown its comparable or superior efficacy against comparators, including third-generation cephalosporin and other β -lactams [42][43][44][45][46][47][48][51][52][53][54][55][56][57][58][59][60][61][62][63][64][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]84,[87][88][89][90]99] . Results of these studies indicated cefepime as safe and well-tolerated in both adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…In surgical patients, cefepime (2 g b.i.d.) does not significantly increase the risk of gastrointestinal colonization by Candida albicans [43] .…”
Section: Effect On Fecal Fl Oramentioning
confidence: 91%